ANALYSIS OF COMPANY VALUE WITH MODERATION OF CORPORATE SOCIAL RESPONBILITY TO INFLUENCE FINANCIAL PERFORMANCE AND CAPITAL STRUCTURE IN MANUFACTURING - Eliza, Eliza -; Zefriyenni, Zefriyenni; Saludin, Mohamad Nasir; Nasrah, Rasidah; Mulya, Jumiatul (JURNAL ECONOMICA : Research of Economic And Economic Education, 2024)
This research was conducted to examine matters related to the variables studied. The objectives of this research are, 1) To determine the influence of financial performance and capital structure on company value, 2) To determine the influence of capital structure on company value, 3) To determine the influence of financial performance on company value and disclosure of corporate social responsibility as a moderating variable in manufacturing companies, and 4) To determine the effect of capital structure on company value and disclosure of corporate social responsibility as a moderating variable in manufacturing companies listed on the BEI in 2018-2022. The sample for this research is manufacturing companies listed on the Indonesian stock exchange in 2018-2022 which were selected using a purposive sampling method with predetermined criteria. In this research, panel data regression analysis was carried out using the E-EVews 12 software program. The results of this research are, 1) Financial Performance partially has a positive and significant effect on Company Value in Manufacturing Companies on the Indonesia Stock Exchange in 2018-2022, 2) Capital Structure has no partial effect on Company Value in Manufacturing Companies on Indonesia Stock Exchange in 2018-2022, 3) Financial Performance does not have a significant effect on Company Value which is partially moderated by Corporate Social Responsibility in Manufacturing Companies on the Indonesian Stock Exchange in 2018-2022, and 4) Capital Structure partially does not has a significant effect on Company Value which is moderated by Corporate Social Responsibility in Manufacturing Companies on the Indonesia Stock Exchange in 2018-2022.